CV automan automation and management of curriculum vitae (CV) documents - Ampo, Criselle Zion Tuliao (2011)
In seeking out employment, there is a need for an individual to hand out various kinds of curriculum vitae (CV) t his employer, depending on the type of company or position he is applying for Considering this and the volumes of information at hand., the most tedious part in constructing a good CV, i sthe ordering of the headings and all information under it every time you make a new variant and this is the problem the other online CV makers failed to address. With CV Automan, the user can manage his personal information accordingly and can create his CV automatically through integration of the information stored in the system with the template provided by the system. Aside from this, CV Automan also offers a convenient way of keeping record and organizing one's academic and work accomplishments. It allows its users to input and manage entries of information, and to upload and download files. CV Automan only requires its users to register to the system to avail its services.